Modeling of contact stresses and evaluation of wear life of a valve mechanism guide with lubricating grooves - Holenko, K.E.; Vychavka, A.A.; Dykha, M.O.; Dytyniuk, V.O. (Problems of Tribology, 2024)
Valve guides are crucial for maintaining proper alignment, positioning, and valve stem clearance as it moves in the cylinder head. Valve bushings are subjected to load and sliding friction; with excessive wear of the guides, the engine begins to consume oil and the valve mechanism becomes noisy. This paper proposes the use of a special knurling to restore and increase the wear resistance of guide bushings. The profile tool is designed to restore valve guides by rolling a spiral groove on the inner surface of the sleeve. After applying this technology, a spiral oil-retaining profile remains on the surface of the sleeve bore. . Using the Solid model, the effect of changing the geometry of the guide bore by the lubricating grooves on the maximum and average stress indices in the guide-valve contact was analyzed. It was found that the maximum stresses of the model with grooves are lower than those of the model with a smooth guide surface. Based on the finite element model, the durability of the valve-guide pair with oil-retaining grooves was analyzed and it was determined how many cycles the contact surface of the guide can withstand. It was established that by reducing the contact pressure, the actual resource of the guide with grooves increased.